Pd-Catalyzed direct C–H arylation of pyrrolo[1, 2-a]quinoxalines. Issue 4 (7th January 2022) - Hao, Di; Yang, Zhen; Liu, Yali; Li, Yang; Li, Chuntian; Gu, Yanlong; Vaccaro, Luigi; Liu, Jichang; Liu, Ping
Abstract : An efficient Pd-catalyzed direct C–H arylation of pyrrolo[1, 2- a ]quinoxalines with aryl iodides is described, providing a series of 1-arylated and 1, 3-diarylated pyrrolo[1, 2- a ]quinoxalines in good yields. Abstract : An efficient Pd-catalyzed direct C–H arylation of pyrrolo[1, 2- a ]quinoxalines with aryl iodides is described, providing a selective route toward a series of 1-arylated and 1, 3-diarylated pyrrolo[1, 2- a ]quinoxalines in good yields. This method features a broad substrate scope, good functional group tolerance and gram-scale synthesis. Furthermore, the C3-thiocyanation of the arylated product is also achieved. We believe that these novel aryl-substituted pyrrolo [1, 2- a ]quinoxalines will have a variety of applications in organic synthesis and medicinal chemistry.